2021
DOI: 10.1136/bjophthalmol-2021-319165
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of swept source optical coherence tomography classification algorithms for detection of gonioscopic angle closure

Abstract: PurposeTo evaluate the performance of swept source optical coherence tomography (SS-OCT) to detect gonioscopic angle closure using different classification algorithms.MethodsThis was a cross-sectional study of 2028 subjects without ophthalmic symptoms recruited from a community-based clinic. All subjects underwent gonioscopy and SS-OCT (Casia, Tomey Corporation, Nagoya, Japan) under dark room conditions. For each eye, 8 out of 128 frames (22.5° interval) were selected to measure anterior chamber parameters nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Nongpiur et al established a stepwise logistic regression model with six ASOCT parameters to diagnose angle closure 95 % of the time [ 32 ]. Tan et al demonstrated that the combined parameters of ACA, LV, and IC derived from the horizontal meridian scans could achieve an AUC of 0.88 in detecting angle closure [ 33 ]. The variations in predictive efficacy between our study and others may stem from differences in patient demographics, disease severity, angle-closure mechanisms involved, and the selection of variables used for constructing the models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nongpiur et al established a stepwise logistic regression model with six ASOCT parameters to diagnose angle closure 95 % of the time [ 32 ]. Tan et al demonstrated that the combined parameters of ACA, LV, and IC derived from the horizontal meridian scans could achieve an AUC of 0.88 in detecting angle closure [ 33 ]. The variations in predictive efficacy between our study and others may stem from differences in patient demographics, disease severity, angle-closure mechanisms involved, and the selection of variables used for constructing the models.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to IOP, which is the main parameter in the early development of screening tests for glaucoma, structural or functional abnormality diagnostic tests are now widely used [ 20 , [32] , [33] , [34] , [35] ]. In PACD, diagnostic tests based on structural changes in the anterior segment are more appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior segment imaging was performed using swept-source anterior segment optical coherence tomography (AS-OCT, CASIA2, Tomey corporation, Nagoya, Japan), as described previously ( 11 , 12 ). The AS-OCT parameters were measured by horizontal scan across the pupil center, including ACD, anterior chamber width (ACW), crystalline lens rise (CLR), iris concavity (IC), iris concavity ratio (ICR), iris thickness at 750 μm from the scleral spur (IT750) and postoperative vault.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to the complexity of the interaction between variables in clinical data, traditional biostatistical methods are limited in capturing hidden information. This information contains complex multivariate information that ML can capture more effectively than traditional methods [16,18,19]. Moreover, various ML methods such as multivariate adaptive regression splines (MARS) can provide helpful insights regarding the captured information.…”
Section: Introductionmentioning
confidence: 99%